1991
DOI: 10.1159/000158892
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant Effect of Chemotactic Peptides on Rabbit Vascular Strips: Evidence for Nitric Oxide Release from a Nonendothelial Source

Abstract: Two distinct peptides, C5a and f-Met-Leu-Phe (FMLP), that are chemotactic for phagocytic leukocytes affect profoundly the circulation in various in vivo systems. These peptides are known to relax strips of rabbit isolated blood vessels, the portal vein and pulmonary artery. In the present study, the effect of recombinant human C5a (2.5–25 nM) was examined and found to be qualitatively similar to that previously reported for FMLP. Indomethacin completely or partially inhibited the vasorelaxations induced by eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This observation has implications apart from MMP-9 activation because nitric oxide can evoke relaxation of blood vessels resulting in increased tissue edema. Indeed it has been observed that C5a can induce relaxation of pulmonary arteries and portal veins even after the endothelial linings were removed suggesting that C5a can exert its effects through elaboration of secondary mediators, one of which could be nitric oxide [45].…”
Section: Discussionmentioning
confidence: 99%
“…This observation has implications apart from MMP-9 activation because nitric oxide can evoke relaxation of blood vessels resulting in increased tissue edema. Indeed it has been observed that C5a can induce relaxation of pulmonary arteries and portal veins even after the endothelial linings were removed suggesting that C5a can exert its effects through elaboration of secondary mediators, one of which could be nitric oxide [45].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the competition binding assays with the cloned C5a rabbit receptor correlated well with the vasorelaxant effects of the C5a analogues on the rabbit pulmonary artery and portal vein, as the order of agonist potency was retained (C5a>Ac‐YSFKPMPLaR; Figure 4). The relaxant effect of C5a on the portal vein and pulmonary artery isolated from normal rabbits has been previously characterized, and is mainly prostaglandin‐dependent (Petitclerc & Marceau, 1991). The precise cell type responsive to the anaphylatoxin has not been determined, but, by analogy with muscular arteries of the rabbit, a low density subendothelial population of resident macrophages may be involved (Malinauskas et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit vascular strips were prepared as described (Petitclerc & Marceau, 1991) and were suspended in 5 ml tissue baths containing Krebs solution (Petitclerc et al ., 1996). Their responses to agents were recorded using isometric transducers (model 52‐9545, Harvard Bioscience, South Natick, MA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, in some experiments using relatively high concentrations of the activators in vitro, fMLP produced vessel relaxation and nitric oxide release, and PMA has depressed endothelium-dependent reactions. 32 -* 3 Such phenomena are most unlikely to be significant in our experiments. Nevertheless, we performed a special investigation of PMA and fMLP effects on the MCA reactivity after intracarotid injection in leukocyte-depleted animals.…”
Section: Discussionmentioning
confidence: 69%